The Mexican Ombudsman; thoughts about the function, challenges and outlook of the National Human Rights Commission - Roccatti V., Mireille (Revista Mexicana de Política Exterior, 2022)
With forms, duties and obligations that vary from country to country, the Ombudsman is a mechanism that seeks to ensure better, fast, effective defense of individual human rights against public power in general, and the government in particular. The National Commission on Human Rights of Mexico (NCHR), Mexican Ombudsman, was created in 1990; its essential objective is the protection, observance, promotion, study and broadcasting of the human rights established in the national legal system. In this essay, the author describes the functions, duties, obligations and organization of the NCHR and analyzes the foundations that sustain its existence (such as its independence, autonomy and impartiality, among other things). She also provides reflections on some of the challenges Mexican society faces in this area, such as the promotion of a culture of respect for human rights.